The Effect of Blended Learning with a Collaborative Problem Solving Approach on Students' Cognitive Learning Outcomes and Collaboration Skills in Science Learning - Bonitasya, Dena Alseptina; Widiyatmoko, Arif; Sovansophal, Kao (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2021)
This research aims to determine the effect of blended learning with a collaborative problem-solving approach on students' cognitive learning outcomes and collaboration skills in science learning. This research is a quasi-experimental method using posttest-only control group design with a cluster random sampling technique. Data were obtained from the posttest scores and observation sheets. Using t-test calculation analysis, the results showed that there was a significant effect on the cognitive learning outcomes of experimental class students in the form of a significant increase after learning using blended learning with a collaborative problem-solving approach (tcount = 3.908 with a significance level of 5% dk = 62). The results of the experimental class collaboration skill observations show one indicator is in the “very good category”, and four indicators are in the “good category”, while in the control class there is only one indicator that is in the “good category” and four indicators are in the “bad category”. The results show that there is a significant effect of blended learning with a collaborative problem-solving approach on students' collaboration skills.